Pneumonia caused by SARS-COV-2: diagnosis and treatment in outpatient settings - V. P. Melnyk; O. V. Panasiuk; H. V. Sadomova-Andrianova; I. V. Antoniuk; I. O. Sliusarchuk; H. Ya. Solonynka (Zaporožskij Medicinskij Žurnal)
The aim of the study was identifying the features of infection in the site, clinical course of the disease, amount and frequency of patient examinations, family doctor communications and treatment of patients with pneumonia caused by SARS-Cov2.